(untitled) - Noble, David F. (New York, 1984)
Focusing on the postwar automation of the American metal-working industry--the heart of the modern industrial economy--this is a provocative study of how automation has assumed a critical role in America. David Noble argues that industrial automation--more than merely a technological advance--is a social process that reflects very real divisions and pressures within our society. The book explains how technology is often spurred and shaped by the military, corporations, universities, and other mighty institutions. Using detailed case studies, Noble also demonstrates how engineering design is influenced by political, economic, and sociological considerations, and how the deployment of equipment is frequently entangled with certain managerial concerns
Keywords: Tự động hóa,Automation; Khía cạnh xã hội,Social aspects; Hoa Kỳ,United states